(untitled) (Research, Society and Development, 2020)
Endodontics is the specialty that covers the control of inflammation of the root canal, the etiology, diagnosis, prevention and therapeutic intervention of diseases associated with the pulp. The objective of the present study is to highlight the current concepts related to the use of bioceramic materials in dentistry. This is a literature review article, developed through a bibliographic survey in the databases Medline, PubMed, Scielo and Periodicos CAPES. The present study showed a gradual increase in research related to bioceramic cements, which may attribute this interest to the importance of having a constant search for improvement of the techniques and materials used to recover oral health. In addition, a broad clinical applicability of these materials in Endodontics was highlighted, due to the evidence found regarding the advantageous properties, such as their excellent biocompatibility, ability to bond to dentin, good radiopacity, better handling conditions, appropriate setting time, bactericidal activity, bioactivity and still, do not cause stains in dental structures, characteristics sought for a restorative material to be efficient.